A new species of Oryctanthus (Loranthaceae) from Colombia - Carmona-Gallego, Isabel; Murillo-Serna, Jhon S.; Roldán, Francisco J.; Alzate-Guarín, Fernando (Phytotaxa, 2020)
A new species of the hemiparasitic genus Oryctanthus from Colombia is described and illustrated. This species is known only from two nearby localities and it can be distinguished from similar species by its terete stems being grayish at maturity, coriaceous leaves with secondary inconspicuous venation and completely furfuraceous inflorescence peduncles, which are 3 or 4 times longer than the fertile portion of the inflorescence. Taxonomic affinities of this species and its conservation status are also discussed.